Improving physical education in higher education institutions in the Philippines: Examining teachers' roles and perceptions in the implementation of CHED Memo No. 39, S. 2021 - Palomaria, Julie Anne R; Aquino, John Michael D (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
This paper examined the implications of the Commission on Higher Education Memorandum Order No. 39, Series of 2021 on the roles and perceptions of physical education teachers. The study wants to gain a better understanding of the implications of the CHED memo on physical education teachers. This study employed a qualitative research approach in a phenomenological approach to understand the experiences of PE teachers with regards to the implementation of mentioned CMO. A purposive sample of 12 respondents made up of 9 males and 3 females were selected to answer the interview guide to gather the necessary data. Thematic analysis was the analytical techniques used to analyze the data. Ethical considerations were taken into account to ensure the trust and confidentiality of the respondents. The results revealed the positive impact of CMO 39 on higher learning institutions, including increased access to quality higher education for students, improved teaching, learning, research outcomes, and the development of a more inclusive environment. The research revealed that the implementation of the program was successful in terms of increasing student engagement and positive learning outcomes. It also highlighted the importance of teacher involvement in helping to create an effective learning environment for students. This research provides further evidence of the impact of teacher involvement in the successful implementation of educational programs, emphasizing the need for teacher support in order to ensure that students are able to achieve their learning goals.